3D object hiding using three-dimensional ptychography. (24th August 2016) - Zhang, Jun; Wang, Zhibo; Li, Tuo; Pan, An; Wang, Yali; Shi, Yishi
Abstract: We present a novel technique for 3D object hiding by applying three-dimensional ptychography. Compared with 3D information hiding based on holography, the proposed ptychography-based hiding technique is easier to implement, because the reference beam and high-precision interferometric optical setup are not required. The acquisition of the 3D object and the ptychographic encoding process are performed optically. Owing to the introduction of probe keys, the security of the ptychography-based hiding system is significantly enhanced. A series of experiments and simulations demonstrate the feasibility and imperceptibility of the proposed method.